Estudio comparado sobre transparencia y derecho de acceso en el ámbito internacional y su influencia en España - Manuel Palomares Herrera (Universidad Hemisferios, 2017)
In order to understand and assimilate the current evolution and the international scope of public transparency and the right of access to public information holistically today, a study of an international set of norms of different dimensions is proposed. To this end, systemically, a compilation and classification of international standards, declarations, provisions and resolutions is carried out first, and secondly a European level in Community declarations, directives and own resolutions. To this follows a commentary and a florilegio that brings to light the current situation of the same from the global to the community. The study concludes in a general overview of what lies in the direction of an emerging right fundamental right of access to public information, the trend and evolution of public transparency on comparative law in which they are reflected in the Recent developments in each field of law.